Numerical evaluation on indoor environment quality during high numbers of occupied passengers in the departure hall of an airport terminal. (1st July 2022) - Zhao, Yu; Feng, Yao; Ma, Liangdong
Abstract: The rapid development of airports and the rapid spread of coronavirus disease 2019 (COVID-19) have brought increased attention to indoor environment quality, airflow organization, key pollutant dispersion, and ventilation modes in airport terminals. However, the characteristics of these parameters, especially carbon dioxide (CO2 ) and aerosol diffusion, are not fully understood. Therefore, in this study, the airflow patterns; CO2 and aerosol dispersion; and several thermal environment indices, including temperature, wind velocity, and predicted mean vote (PMV), of an airport terminal departure hall with high numbers of occupied passenger were numerically evaluated using the realizable k-ε and passive scalar models. The efficacies of three common ventilation modes, namely, up-supply and up-return, up-supply and down-return with different sides, and up-supply and down-return with the same side, were evaluated based on the CO2 removal efficiency and spreading range of aerosols. The results indicated that under high numbers of occupied passenger conditions, these ventilation modes vary slightly, with respect to create a comfortable and healthy environment. In particular, the up-supply and down-return with different sides mode was the best among the modes considered, when comparing the indices of temperature, wind speed PMV, and CO2 emission efficiency. Conversely, with respect to decreasing the risk of aerosol exposure, the up-supply and down-return with the same side mode was the best. Overall, the results from this study provide fundamental information for predicting CO2 and aerosol exposure levels and will act as a reference for the design and operation of ventilation systems in airport terminal buildings. Highlights: Evaluation of air distribution in airport terminal during high occupied passengers. Analysis of the risk of aerosol exposure in the department hall. Up-supply and down-return with different sides mode dilutes CO2 effectively. Up-supply and down-return with same side mode prevents aerosol diffusion well.